Imaging biomarkers of behavioral impairments: a pilot micro-positron emission tomographic study in a rat electrical post-status epilepticus model - Dijk, Roelof Maarten van; Liberto, Valentina Di; Brendel, Matthias; Waldron, Ann Marie; Möller, Christina; Gildehaus, Franz Josef; Ungern-Sternberg, Barbara von; Lindner, Magdalena; Ziegler, Sibylle; Hellweg, Rainer; Gass, Peter; Bartenstein, Peter; et al. (Epilepsia, 2018)
Objective In patients with epilepsy, psychiatric comorbidities can significantly affect the disease course and quality of life. Detecting and recognizing these comorbidities is central in determining an optimal treatment plan. One promising tool in detecting biomarkers for psychiatric comorbidities in epilepsy is positron emission tomography (PET). Methods Behavioral and biochemical variables were cross-correlated with the results from two μPET scans using the tracers [18F]fluoro-2-deoxy-D-glucose ([18F]FDG) and 2′-methoxyphenyl-(N-2′-pyridinyl)-p-18F-fluoro-benzamidoethylpiperazine ([18F]MPPF) to explore potential biomarkers for neurobehavioral comorbidities in an electrically induced post-status epilepticus rat model of epilepsy. Results In rats with epilepsy, μPET analysis revealed a local reduction in hippocampal [18F]FDG uptake, and a local increase in [18F]MPPF binding. These changes exhibited a correlation with burrowing as a “luxury” behavior, social interaction, and anxiety-associated behavioral patterns. Interestingly, hippocampal [18F]FDG uptake did not correlate with spontaneous recurrent seizure activity. Significance In the electrically induced post-status epilepticus rat model, we demonstrated hippocampal hypometabolism and its correlation with a range of neurobehavioral alterations. These findings require further confirmation in other preclinical models and patients with epilepsy and psychiatric disorders to address the value of [18F]FDG uptake as an imaging biomarker candidate for psychiatric comorbidities in patients as well as for severity assessment in rodent epilepsy models.
Gesehen am 13.03.2020